A Pictorial Key for Culex pipiens Complex (Diptera: Culicidae) In Iran - Hossein Dehghan; Javid Sadraei; Seyed Hassan Moosa-Kazemi; Esmail Abolghasemi; Hassan Solimani; Ahmad Jaffari-Nodoshan; Mohammad Hassan Najafi (Tehran University of Medical Sciences, 2016)
Background: The aim of this study was to design pictorial key and taxonomic literature of Culex pipiens complex in Iran. Methods: Larvae were collected using standard dipping methods in 13 randomly selected areas of Bushehr, Hamedan, Kerman, Khorasan-e-Razavi, Khuzistan, Mazandaran, Tehran, Sistan and Baluchistan and Yazd Provinces from April 2009 to October 2010. The data were analyzed using SPSS Ver. 11.5. Results: Culex pipiens larvae were identified based on the Seta 1 of the abdominal segments III-IV in north and central parts of Iran. This diagnostic character had some variation among the Cx. quinquefasciatus collected from south of the country. The identification value of intersection of costa, subcosta and bifurcation of R2+3 of female veins, was calculated as 90-100 % for Cx. pipiens. This diagnostic character was varied among the Cx. quinquefasciatus specimens. The male genitalia found as the main characters to distinguish of Cx. quinquefasciatus from Cx. pipiens. Conclusion: It is necessary more studies on the behavior and genetic variations of Cx. pipiens complex in Iran.